From commanding to serving athletes: Nurturing the coach-athlete relationship - Minjung, K.; Yukyoum, K.; Won, D. (International Journal of Sports Science & Coaching, 2018)
As one of the emerging themes in research on sport management leadership, servant leadership focuses on facilitating individual growth and moral development. The present study tested a hypothesized research model that demonstrates support for the effects of a head coach's servant leadership on athletes' ethical development and team outcome confidence through the quality that characterizes the coach-athlete relationship. We recruited 347 student-athletes of football teams and men's basketball teams who play under the Division I system of the US National Collegiate Athletic Association. Whereas the quality of the coach-athlete relationship partially mediated the association between servant leadership and ethical development, it fully mediated the paths from servant leadership to team outcome confidence. This study provides empirical support for the positive influence of servant leadership behaviors and advances an improved understanding of the role played by the aforementioned relationship quality in coaching leadership research.